Peleburan Skrap Aluminium pada Tungku Krusibel berbahan Bakar Batubara Hasil Proses Aglomerasi Air-Minyak Sawit - Nukman Nukman; Agung Mataram; Irsyadi Yani (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2015)
Smelting aluminum scrap in a small capacity can be done on a simple furnace crucible. As fuel furnaces used type of semi-anthracite coal briquettes, bituminous and sub-bituminous from Tanjung Enim which has been through the washing process by agglomeration method using water-oil palm. Calorific value, the contents of water and hydrogen calculated in the energy balance. Aluminum scrap smelted at a temperature 1023oK. Furnace by coal briquette which has a 23.38% efficiency,, crucible can melt 50 kg of aluminum scrap by 6.47 kg of briquettes for 1 hour 46 minutes.Keywords:coal briquette, coal aglomeration, aluminum scrap, crusible furnace